Using video for reconstruction in SfM. The Capo d’Omo Tower on Mount Argentario - Fabio Lanfranchi; Piero Barlozzini; Luca Martelli (Disegnare con)
In the context of 3D surveying methods, the role of drones is growing in importance. The capacity to approach the object and acquire both photos and videos from points that are highly inaccessible from the ground make these devices an efficient tool on the architectural and territorial scales, whether anthropized or not. Even more widespread are so-called unmanned aircraft systems (UAS), inoffensive and lighter than 250 g, due to the simplification of the related standards and continued improvements in their acquisition devices. The most advanced photo-modelling programs are now able to process video clips directly, automatically selecting the photos suitable for input in scale-invariant feature transform (SIFT) and speeded up robust features (SURF) algorithms, essential aspects of structure from motion (SfM). This technological progress constitutes a significant jump in automating SfM investigations, especially when made with UAS. With this background, the case study presented here is the sighting tower of Capo d’Omo, situated atop Mount Argentario near Grosseto. Two questions are addressed: assessment of the metric reliability of a model automatically reconstructed from video clips (in this case, taken from an UAS) through comparison with a model acquired from an active sensor device; and a study of its potential and possible use in the SfM workflow, also considering the limited software and hardware requirements necessary to process this type of product. DOI: https://doi.org/10.20365/disegnarecon.30.2023.6